PENGARUH IMPLEMENTASI GOOD HOUSEKEEPING DAN KESELAMATAN KERJA TERHADAP KINERJA BISNIS : STUDI KASUS PADA PT KPI RU III PLAJU - Triadi Lukito; Lamtiur H. Tampubolon; Heru Prasadja (PT. Hasba Edukasi Mandiri, 2025)
The oil and gas industry is a strategic sector that requires systematic approaches in workplace management through Good Housekeeping and occupational safety implementation to achieve optimal business performance. This study aims to comprehensively analyze the influence of Good Housekeeping and occupational safety implementation on business performance at PT Kilang Pertamina Internasional (KPI) RU III Plaju. The research employed a quantitative approach with random sampling technique involving 125 respondents from a population of 919 employees. Data were collected through Likert scale questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) and multiple linear regression through SPSS 30. The results demonstrate that Good Housekeeping significantly influences occupational safety (t-value 6.877 > t-table 1.979; p = 0.000) with regression coefficient of 0.383. Occupational safety shows highly significant influence on business performance (t-value 15.844 > t-table 1.979; p = 0.000) with regression coefficient of 1.013 and explains 76.9% of business performance variation. Good Housekeeping also directly influences business performance (t-value 2.215 > t-table 1.979; p = 0.029) with regression coefficient of 0.103. This study confirms that integrated implementation of Good Housekeeping and occupational safety provides dual benefits through simultaneous improvement of occupational safety and business performance, with recommendations for developing comprehensive and sustainable implementation strategies.